2010
DOI: 10.1016/j.tox.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve and brain differ in their capacity to resolve N,N-diethyldithiocarbamate-mediated elevations in copper and oxidative injury

Abstract: Previous studies have demonstrated that N,N-diethyldithiocarbamate (DEDC) elevates copper and promotes oxidative stress within the nervous system. However, whether these effects resolve following cessation of exposure or have the potential to persist and result in cumulative injury has not been determined. In this study, an established model for DEDC myelin injury in the rat was used to determine whether copper levels, oxidative stress, and neuromuscular deficits resolve following the cessation of DEDC exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…DEDC has been shown to increase lipid peroxidation and induce the antioxidant enzymes superoxide dismutase 1 (SOD1), glutathione S‐transferase–α (GST‐α), and heme oxygenase‐1 (HO‐1) in sciatic nerves of rats (Valentine et al . ). Sodium methyldithiocarbamate has been shown to deplete intracellular GSH, induce antioxidant enzymes sulfiredoxin, peroxiredoxin, and isocitrate dehydrogenase, and alter the inflammatory cytokine profile of peripheral macrophages in mice (Pruett et al .…”
Section: Discussionmentioning
confidence: 97%
“…DEDC has been shown to increase lipid peroxidation and induce the antioxidant enzymes superoxide dismutase 1 (SOD1), glutathione S‐transferase–α (GST‐α), and heme oxygenase‐1 (HO‐1) in sciatic nerves of rats (Valentine et al . ). Sodium methyldithiocarbamate has been shown to deplete intracellular GSH, induce antioxidant enzymes sulfiredoxin, peroxiredoxin, and isocitrate dehydrogenase, and alter the inflammatory cytokine profile of peripheral macrophages in mice (Pruett et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, in the present study, it was observed that EGCG toxicity was protected in mice with supra-physiological levels of Cu involving modulation of serum Cp activity and ROS generation. Not only does administration of DEDTC or disulfiram, which is metabolized to DEDTC in vivo, significantly increase hepatic Cu levels [ 36 , 39 , 40 , 41 ], it also significantly decreases Cu levels or Cp activities in blood [ 36 , 42 , 43 ]. It is possible that because of the low Cu and Cp activities, more EGCG was translated into liver and oxidized with ROS generation resulting into hepatotoxicity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While those previous proteomic studies are consistent with inhibition of E1 through electrophilic adduction, other studies report that E1 activity is dependent on the redox status of the cell, suggesting that dithiocarbamates may also inhibit E1 through elevated oxidative stress. , Dithiocarbamates form metal complexes that vary in their solubility and redox activity depending upon the polarity of the nitrogen substituents and the redox potential of the metal, respectively. , Dithiocarbamates readily bind copper and dithiocarbamates with nonpolar nitrogen substituents, including DEDC and N,N -dimethyldithiocarbamate (DMDC), form redox active copper complexes that cross cell membranes, partition into lipid compartments, and promote oxidative injury. This property has been demonstrated in animal models through elevations of copper, lipid peroxidation, protein oxidative injury, and increased apoptosis. In the study presented here, we investigated the relative contribution of covalent adduction and oxidative stress in the dithiocarbamate-mediated inhibition of E1 in HEK293 cells.…”
Section: Introductionmentioning
confidence: 55%
“…Earlier studies in cell models suggest that E1 activation is redox sensitive, and in vivo studies have demonstrated that dithiocarbamates complex metals and cross cell membranes, potentially increasing intracellular levels of redox active metals. 16 , 23 , 24 , 29 Thus, we reasoned that exposure to ziram and DMDC may be contributing to the observed E1 inhibition by promoting intracellular oxidation, a mechanism that could potentially be shared by many environmental agents and disease conditions. Therefore, our results prompted us to investigate this alternative mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation